Levels of MUC1 in tumours and serum of patients with different sub-types of squamous cell carcinoma of the head and neck - Boldrup, Linda; Coates, Philip; Gu, Xiaolian; Wang, Lixiao; Fåhraeus, Robin; Wilms, Torben; Sgaramella, Nicola; Baumgarth, Jonathan; Norberg-Spaak, Lena; Nylander, Karin (Oncology letters, 2020)
Mucin 1 (MUC1) is a membrane-bound and secreted glycoprotein that has a protective role in surface epithelia. We recently demonstrated that MUC1 mRNA expression was upregulated in tumour-free tongue tissues adjacent to squamous cell carcinoma of the oral tongue (SCCOT) compared with that in the tumour tissues. The present study investigated MUC1 protein in SCCOT tissue and serum from patients with squamous cell carcinoma of the head and neck (SCCHN) at different sub-sites. The results from immunohistochemistry demonstrated that all SCCOT tissues expressed MUC1; however, the protein levels were not correlated with MUC1 mRNA levels in the same tumours. Furthermore, serum MUC1 level was lower in patients with SCCOT, tonsil SCC and gingival SCC compared with that in healthy subjects; however, the difference was only significant for patients with SCCOT (P=0.0421). No correlation was seen between MUC1 level in tumour tissues and MUCI level in serum from the same patients. The absence of correlation between MUC1 protein and mRNA levels in SCCOT tissues emphasized the importance of validating genomic data in clinical samples. Although significant MUC1 downregulation was observed in the serum of patients with SCCOT, there was a large variation within the groups, suggesting that MUC1 may not be used as a biomarker for these types of tumors.
Keywords: squamous cell carcinomas of the oral tongue; blood markers; mucin 1; prognosis; microarray; validation